AKIBAT HUKUM PENGGUNAAN KARYA CIPTA MUSIK DAN LAGU TANPA IZIN - Hulman Panjaitan (to-ra, 2020)
Copyright is very important part of Intelectual Property Right. That is particularly in the field creation of Copyright about song and music, its offence extremely concerned and serious in Indonesia. Copyright is the exclusive right or special right which has meaning that other people cannot take all advantages on the right as from creator economy for its creatures without any license creator or copyright holders legitimate. The Consequences are in every utilization of music for Commercial Business activities and or for purpose relates with business/aims commercial such as Café, Hotel, restaurant and others, must request permission first to the creator and or copyright holder over the use of creation in regards about the song and music. Keywords : Utilization of Copyright without permission.